2022
DOI: 10.12678/1089-313x.121522f
|View full text |Cite
|
Sign up to set email alerts
|

Dance, Music, and Social Conversation Program Participation Positively Affects Physical and Mental Health in Community-Dwelling Older Adults: A Randomized Controlled Trial

Abstract: Introduction: As the world population ages, practitioners use community-engaged interventions to help older adults stay healthy. Engaging in arts programs (e.g., dance or music) reportedly improves physical and mental health, but little research exists examining these effects in community-dwelling older adults. Our purposes were to examine how taking part in 10-week, twice per week community arts programs (dance and music) and control (social conversation) affected physical and mental health in community-dwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) studies have shown that structural changes, such as the decline in the volume of the prefrontal areas and hippocampus during aging, can predict a person’s cognitive performance ( Raz et al, 1997 ; Morrison and Baxter, 2012 ). New approaches tested to maintain or improve cognitive abilities during aging include hormonal supplementation ( Foster et al, 2003 ), magnetic brain stimulation, oxygen therapy ( Yang C. et al, 2023 ), cognitive stimulation using computer-assisted programs ( Curlik 2nd and Shors, 2013 ; Clemenson and Stark, 2015 ; Nebot et al, 2022 ), guided exercise, music and dance therapy ( Thumuluri et al, 2021 ; Aguinaga et al, 2022 ; Ambegaonkar et al, 2022 ; Kennedy et al, 2022 ; Li et al, 2022 ; Rodziewicz-Flis et al, 2022 ; Vega-Avila et al, 2022 ; Wang et al, 2022 ; Zhu Y. et al, 2022 ; Blanco-Rambo et al, 2023 ), and diets containing natural antioxidant compounds ( Kumar et al, 2012 ; Maki, 2012 ; Smith et al, 2014 ; Barreto et al, 2017 ; Phipps et al, 2021 ; Tao et al, 2023 ; Tchekalarova and Tzoneva, 2023 ).…”
Section: Memory Loss During Agingmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies have shown that structural changes, such as the decline in the volume of the prefrontal areas and hippocampus during aging, can predict a person’s cognitive performance ( Raz et al, 1997 ; Morrison and Baxter, 2012 ). New approaches tested to maintain or improve cognitive abilities during aging include hormonal supplementation ( Foster et al, 2003 ), magnetic brain stimulation, oxygen therapy ( Yang C. et al, 2023 ), cognitive stimulation using computer-assisted programs ( Curlik 2nd and Shors, 2013 ; Clemenson and Stark, 2015 ; Nebot et al, 2022 ), guided exercise, music and dance therapy ( Thumuluri et al, 2021 ; Aguinaga et al, 2022 ; Ambegaonkar et al, 2022 ; Kennedy et al, 2022 ; Li et al, 2022 ; Rodziewicz-Flis et al, 2022 ; Vega-Avila et al, 2022 ; Wang et al, 2022 ; Zhu Y. et al, 2022 ; Blanco-Rambo et al, 2023 ), and diets containing natural antioxidant compounds ( Kumar et al, 2012 ; Maki, 2012 ; Smith et al, 2014 ; Barreto et al, 2017 ; Phipps et al, 2021 ; Tao et al, 2023 ; Tchekalarova and Tzoneva, 2023 ).…”
Section: Memory Loss During Agingmentioning
confidence: 99%
“…More specifically, unlike the majority of other types of physical activity, dance is an aesthetic form that allows for creative expression and is socially engaging [8]. Dancing can result in physical benefits comparable with those of formal exercise training [9], and has been found to improve social engagement and HRQOL [7,10,11]. In addition, Keogh and colleagues found that dance improved the emotional, psychological, and physical well-being of individuals [12], and Ambegoankar et al 2022 found that weekly dance sessions had a positive impact on physical health and cognition for community dwelling older adults [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that arts and arts-based activities can positively impact physical and mental health outcomes by fostering creativity and promoting meaningful social engagement, both of which can improve HRQOL [7]. More specifically, unlike the majority of other types of physical activity, dance is an aesthetic form that allows for creative expression and is socially engaging [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations